2020
DOI: 10.1177/1350650120915136
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of geometrical parameters of crosshatched texture for enhanced tribological performance under biological environment

Abstract: This study optimizes the texture geometry by investigating the individual effect of texture depth and area density of cross hatched texture to improve the tribological performance of hip implant at normal walking speed. Texture width was selected conforming to Hertzian contact of Ti6Al4V/ultrahigh molecular weight polyethylene tribo-pair. Crosshatched textures with different depths and area densities were fabricated on polished Ti6Al4V blocks using laser surface texturing technique. Tribology tests were carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
1
7
0
Order By: Relevance
“…Afterward, the authors also optimized the micro-groove parameters such as depth and area density to obtain maximum tribological benefits. 21 They reported a friction reduction of 50% at a groove depth of 5 µm and area density of 25%. In some of recent studies, the authors analyzed the optimum texture shape for various mechanical tribo-systems under different operating scenarios.…”
Section: Introductionmentioning
confidence: 96%
“…Afterward, the authors also optimized the micro-groove parameters such as depth and area density to obtain maximum tribological benefits. 21 They reported a friction reduction of 50% at a groove depth of 5 µm and area density of 25%. In some of recent studies, the authors analyzed the optimum texture shape for various mechanical tribo-systems under different operating scenarios.…”
Section: Introductionmentioning
confidence: 96%
“…Based on insights from previous literature, [32][33][34][35][36] the study aimed to enhance the rationality and practicality of texture arrangement. To accomplish this, we introduced concave textures onto the surface of the metal rotor for preliminary investigation.…”
Section: Specimen Parametersmentioning
confidence: 99%
“…Shangzhen et al 32 performed a texture treatment on cylinder liner-piston rings and found that the regular distribution of concave texture could effectively improve the lubrication and wear performance of the frictional pair. Dan et al 33 and Kashyap and Ramkumar 34 studied the effect of texture area ratio on the effect of wear reduction and drag reduction and found that different texture area ratios have different effects on the tribological properties of the friction pair. He et al 35 comprehensively compared the stress and temperature variations of three micro-texture shapes and concluded that the circular pit micro-texture was the most effective in reducing friction.…”
Section: Introductionmentioning
confidence: 99%
“…Through the AM, it was possible to obtain customized devices on the needs of patients and therefore more effective. Moreover, in order to guarantee a longer life cycle of the prostheses and an appropriate lubrication, the application of nanostructured coatings and surface processing was studied [14][15][16][17], such as the surface laser texturing technique already widely used in other industrial sectors [18,19]. Numerical techniques, such as the Finite Element Method (FEM), have recently been adopted to support experimental studies regarding the calculation of the useful life and the functionality optimization of the prostheses [20].…”
Section: And 30 N) and Five Different Bio-lubricantsmentioning
confidence: 99%